Design and analysis of random multiple access quantum key distribution. Issue 1 (25th February 2020) - Zhang, Yao; Ni, Qiang
Summary: This article proposes a potential application of quantum key distribution in multiuser networks. In modern networks, variety of multiple access technologies are used for multiuser access purposes. In this article, we focus on a type of widely used media access control protocol—carrier‐sense multiple access (CSMA) and analyze the use of carrier‐sense multiple access with collision avoidance (CSMA/CA) for the quantum key distribution in the network. The quantum key generation is based on a successful experiment that implemented the quantum key distribution by using the decoy‐state method. The secret key generation rate as the main indicator of the performance is given, including the relationship between it and the number of stations in the network, and the relationship between the key generation rate and the transmission distance under the multiple access condition as well. In addition, a multiple access quantum key distribution with channel detection protocol is also proposed.